PENGARUH JENIS PELARUT DAN RASIO BAHAN DENGAN PELARUT TERHADAP KANDUNGAN SENYAWA FENOLIK DAN AKTIVITAS ANTIOKSIDAN EKSTRAK BIJI ALPUKAT (PERSEA AMERICANA MILL.) - Rifai, Ginanjar; Rai Widarta, I Wayan; Ayu Nocianitri, Komang (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
This research was conducted in order to determine the type of solvent and ratio between sample and solvent to produce extract avocado seed with the highest antioxidant activity. The experimental design used in this research was a factorial completely randomized design which consisted of two factors. The first factor was the type of solvent consisting of ethanol, methanol, and acetone. The second factor was ratio between sample and solvent of 1:5, 1;10, and 1:15. The treatment was repeated three time to obtain 27 units of the experiment. Data were analyzed with analysis of variance, followed by Duncan test. The results show that the solvent of acetone and ratio between sample and solvent of 1:15 was highest antioxidant activity with total phenolic 803.60 mg/100g, IC50 was 540.95 ppm, and yield 41.36%.